2011
DOI: 10.1682/jrrd.2010.05.0104
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis of posttraumatic stress disorder screening within specialty clinic setting for OIF/OEF veterans seeking care for neck or back pain

Abstract: Abstract-Escalating prevalence estimates of posttraumatic stress disorder (PTSD) among recently returning Operation Iraqi Freedom/Operation Enduring Freedom (OIF/OEF) veterans highlight the need for early detection and management for reducing chronic mental illness and disability. Because PTSD and chronic pain are common comorbid conditions among veterans, PTSD screening within specialty clinic settings addressing musculoskeletal pain may be of value. This retrospective study evaluated measures of diagnostic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 63 publications
(77 reference statements)
1
26
0
Order By: Relevance
“…The results showed an outstanding AUC value for the ROC curve (0.94), suggesting high ability to discriminate between individuals with and without PTSD. Previous studies with war veterans reported lower AUC values, ranging from 0.88 to 0.90 for the PCL-M 8,12 and from 0.86 to 0.89 for the PCL-C. [9][10][11] Studies with other populations and using other versions of the PCL also reported lower AUC values, ranging from 0.76 to 0.84. 13,14 In addition, the specific AUC for the optimal cutoff point of 49 also showed outstanding discriminatory ability (AUC = 0.88).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The results showed an outstanding AUC value for the ROC curve (0.94), suggesting high ability to discriminate between individuals with and without PTSD. Previous studies with war veterans reported lower AUC values, ranging from 0.88 to 0.90 for the PCL-M 8,12 and from 0.86 to 0.89 for the PCL-C. [9][10][11] Studies with other populations and using other versions of the PCL also reported lower AUC values, ranging from 0.76 to 0.84. 13,14 In addition, the specific AUC for the optimal cutoff point of 49 also showed outstanding discriminatory ability (AUC = 0.88).…”
Section: Discussionmentioning
confidence: 83%
“…This index is more reliable than the other indicators used, namely diagnostic efficiency and positive and negative predictive power, for the identification of the ideal cutoff point regardless of disease prevalence. 27,28,12 Thus, we believe that a cutoff score of 49 should be used with Portuguese Colonial War veterans across other samples and settings, and that no information is needed regarding PTSD prevalence. This cutoff score is similar to that proposed by the authors of the original PCL-M, i.e., 50, 1 and higher than those described in other studies using other PCL versions in war veteran samples (between 28 and 38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Veterans with TBI are also highly represented in case manager caseloads due to the intensity of their TBIrelated treatment needs and treatment needs related to cooccurring conditions, particularly PTSD. The provision of adequate resources to address mental healthcare needs will be particularly important because mental health and psychosocial conditions have been detected in a substantial proportion of OIF/OEF Veterans [24][25]. PTSD has been identified as the most common mental health condition [26] frequently occurring among servicemembers who experienced deployment-related blast and nonblast TBI [27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of Vietnam veterans, the PCL demonstrated excellent test-retest reliability (0.96) and internal consistency (0.97), and adequate sensitivity (0.82) and specificity (0.83) using a cutoff score of 50 . However, more recent studies in veteran populations support the use of a lower cutoff for the PCL (Bliese et al, 2008;Yeager, Magruder, Knapp, Nicholas, & Frueh, 2007);Yeager et al (2007) reported a sensitivity and specificity of 0.81 using a cutoff of 31, versus a sensitivity of 0.53 and a specificity of 0.95 using a cutoff of 50, while a recent study by Dunn et al (2011) reported an optimal cutoff of 44 based on a receiver operating characteristic curve, with a sensitivity of 0.81 and a specificity of 0.83. Differences in the sensitivity and specificity for a given cutoff score and the optimal cutoff score across studies may be due to population characteristics such as the severity of PTSD symptoms, the interrater reliability of the screening instrument, or differences in the "gold standard" diagnostic assessment to which the screening instrument is compared (Warner, 2004).…”
Section: Overview Of Screening Instruments For Identifying Ptsd In MImentioning
confidence: 98%